2021
DOI: 10.1186/s13071-021-04595-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of NbTMP1, a surface protein of sporoplasm, in Nosema bombycis infection

Abstract: Background Nosema bombycis is a unicellular eukaryotic pathogen of the silkworm, Bombyx mori, and is an economic and occupational hazard in the silkworm industry. Because of its long incubation period and horizontal and vertical transmission, it is subject to quarantine measures in sericulture production. The microsporidian life-cycle includes a dormant extracellular phase and intracellular proliferation phase, with the proliferation period being the most active period. This latter period lacks… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…NTT is a key strategy adopted by microsporidia to exploit host cells ( Heinz et al, 2014 ). Zheng et al (2021) reported that the membrane protein of N. bombycis NbTMP1 may get involved in the proliferation of N. bombycis .…”
Section: Discussionmentioning
confidence: 99%
“…NTT is a key strategy adopted by microsporidia to exploit host cells ( Heinz et al, 2014 ). Zheng et al (2021) reported that the membrane protein of N. bombycis NbTMP1 may get involved in the proliferation of N. bombycis .…”
Section: Discussionmentioning
confidence: 99%
“…The produced monoclonal antibodies (mAbs) were harvested and assessed as documented previously (Huang et al ., 2018 a ). The mouse monoclonal antibody isotyping kit (Roche, Switzerland) was employed to assay the subtypes of mAb immunoglobulin G (IgG) as described by the manufacturer (Zheng et al ., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…10,11 As an important intestinal pathogen, N. bombycis can be transmitted horizontally through per os infection as well as vertically from adults to offspring. 12 The pathogen N. bombycis is well adapted to the silkworm gut environment, where it germinates and penetrates the gut epithelium, absorbing nutrients and energy from the host and exporting cytotoxic compounds through the cell membrane. 13 This species has a sophisticated and unique mechanism for infecting host cells, involving a rigid spore wall and a coiled polar tube joined to an anchoring disc at the apical part of the spore.…”
Section: Introductionmentioning
confidence: 99%
“…As an important intestinal pathogen, N. bombycis can be transmitted horizontally through per os infection as well as vertically from adults to offspring 12 . The pathogen N. bombycis is well adapted to the silkworm gut environment, where it germinates and penetrates the gut epithelium, absorbing nutrients and energy from the host and exporting cytotoxic compounds through the cell membrane 13 .…”
Section: Introductionmentioning
confidence: 99%